Pencegahan Kebakaran Saat Aktivitas Bongkar Crude Oil Menggunakan Inert Gas System di Kapal Tanker - Fitri Suprapti; Susanto Susanto; Endra Dody (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2022)
Liquid cargo carried by tankers carries a very high risk of fire, with an explosion. The environment greatly affects the success in minimizing the risk of fire on tankers. The risk of fire hazard can occur at any time, during tank washing, loading, in shipping, and in the discharging process. Combustible material, oxygen and heat in sufficient composition will trigger a fire. Inert gas which has Oxygen (O2) < 8% can be used as a fire prevention solution from cargo spaces. Many fires that occur on tankers occur during cargo operations, loading, discharging and tank cleaning. This research was conducted directly on board the ship through a case study. The study was conducted aboard MT. Gamsunoro operated by PT. Pertamina International Shipping. The number of Inert Gas fans used and the volume of the tank are fixed variables in the operation of the IGS. The parameters measured were the oxygen content of the inert gas in the main line and cargo tank. The working pressure in the cargo hold is also measured to ensure the pressure is higher than atmospheric. The results of the study found that the O2 content of the main channel decreased from 20.9% to 3.3 in 80 minutes. The average O2 content in the tank is 5.34% can be achieved with an average inerting time of 3.3 hours/tank using 1 inert gas fan. The average pressure in the tank is 782.85 mm Hg. These conditions indicate the optimal operation of the inert gas system, so that the disassembly process meets the requirements for fire prevention safety from tanker cargo spaces.